The Estimation of Cuscus Population and Distribution in Teluk Wondama District, West Papua Province, Indonesia - Felayati, Nela Resta; Santoso, Nyoto; Rahman, Dede Aulia (Media Konservasi, 2024)
Cuscus is a marsupial mammal endemic to the eastern part of Indonesia. Populations and their habitats are under pressure due to economic development, population growth and utilization of forest resources. So far, studies on cuscus ecology have mainly focused on protected habitats or conservation areas, this study aims to identify and analyze populations and predict the distribution of cuscus in non-protectes area which is PT Wijaya Sentosa. This research conduct in November 2020 until January 2021 in several land cover categories. The methods used in this study include literature and secondary data studies, field observations using strip-transect and camera trap techniques, interviews using purposive sampling techniques. This study found nine individuals of cuscus from direct observation with strip-transects and two individuals of cuscus from camera trapping. The ground cuscus population (P. gymnotis) had the highest abundance and density, while the common spotted cuscus (S. maculatus) population owned the lowest values. The population structure dominates by male sex and adult age class, and no female sex and young age class were found. Cuscus was more commonly found solitary in the line of observation and not found in every line. The shape of the distribution pattern of the cuscus population at PT Wijaya Sentosa is cluster/aggregated, determined from the value of the dispersion index and the ratio of variance to mean. The most common ground cuscus was found in the 2018 and the 2013 logging area (LOA).